Classical Hollywood Reader. - Neale, Steve (Taylor and Francis, 2012)
The Classical Hollywood Reader brings together essential readings to provide a history of Hollywood from the 1910s to the mid 1960s. Following on from a Prologue that discusses the aesthetic characteristics of Classical Hollywood films, Part 1 covers the period between the 1910s and the mid-to-late 1920s. It deals with the advent of feature-length films in the US and the growing national and international dominance of the companies responsible for their production, distribution and exhibition. In doing so, it also deals with film making practices, aspects of style, the changing roles played by.